Critical view on the usage of C-ring specimen for stress corrosion crack (SCC) test on orthopedic implant : experimental, numerical and analytical approaches - Prawoto, Yunan (2012)
As the failures of orthopedic devices due to stress corrosion cracking (SCC) have become more frequent nowadays, research on this area also has become popular. Many published articles show the basic characterizations and evaluations of the SCC performed based on ASTM standards by using the C-ring sample. This paper discusses stress redistribution during SCC testing. The results show that the stress versus displacement equation presented in the standard is erroneous as the specimen begins to crack. It is only true for a non-cracked specimen. As the crack propagates, the sharpness of the crack tip minimizes the validity of the equation, even when the thickness reduction is taken into account.